Materials, techniques, and pattern design of traditional lekar midrib sticks basket weave patterns: a comparison / Asrol Hasan, Ahmad Fazlan Ahmad Zamri and Nursaffawati Nazihah Azhar - Hasan, Asrol; Ahmad Zamri, Ahmad Fazlan; Azhar, Nursaffawati Nazihah (Faculty of Art and Design, 2024)
Weaving is a handicraft work of art from natural materials that can create a usable product through the ingenuity of human creation. Midrib stick lekar basket is one of the traditional woven crafts that still exists even though its function is no longer as important as it used to be. The study aims to identify the material, technique, and design of the weaving pattern of midrib stick lekar basket craft by comparing different practitioners or communities from three states, namely Kedah, Terengganu and Kelantan. The results of this study will help researchers see the extent to which the use of materials, diversity of techniques and pattern design will form an identity or abnormality in each woven product produced. The material focuses on the materials of coconut midrib sticks and nipa palm midrib sticks, which are very compatible with the woven baskets of lekar midrib sticks. To answer this purpose, research was conducted qualitatively through the field research method to collect, observe and analyze samples of midrib stick lekar baskets from different communities as the primary source of reference in addition to interviews with midrib stick lekar basket weavers. The analysis found that these three states' craft of basket weaving and midrib stick lekar baskets have apparent similarities in manufacturing and processing techniques. The shapes and sizes produced have exhibited different characteristics that have influenced the invention of pattern design and new functional.